X-ray structure of human acid-β-glucosidase, the defective enzyme in Gaucher disease - Dvir, Hay (2003)
Gaucher disease, the most common lysosomal storage disease, is caused by mutations in the gene that encodes acid-β-glucosidase (GlcCerase). Type 1 is characterized by hepatosplenomegaly, and types 2 and 3 by early or chronic onset of severe neurological symptoms. No clear correlation exists between the ∼200 GlcCerase mutations and disease severity, although homozygosity for the common mutations N370S and L444P is associated with non- neuronopathic and neuronopathic disease, respectively. We report the X-ray structure of GlcCerase at 2.0 Å resolution. The catalytic domain consists of a (β/α)(8) TIM barrel, as expected for a member of the glucosidase hydrolase A clan. The distance between the catalytic residues E235 and E340 is consistent with a catalytic mechanism of retention. N370 is located on the longest α-helix (helix 7), which has several other mutations of residues that point into the TIM barrel. Helix 7 is at the interface between the TIM barrel and a separate immunoglobulin-like domain on which L444 is located, suggesting an important regulatory or structural role for this non-catalytic domain. The structure provides the possibility of engineering improved GlcCerase for enzyme-replacement therapy, and for designing structure-based drugs aimed at restoring the activity of defective GlcCerase.